ANALISIS FAKTOR PENYEBAB KEGAGALAN 212 MART DITINJAU DARI LOYALITAS ANGGITA - Irawan Putra, Hari; Supriyanto, Trisiladi; Ayuniyyah, Qurroh (Universitas Ibn Khaldun Bogor, 2023)
The objectives of this study are 1) To find out the cause of the failure of 212 Mart Bojongkulur, 2) To find out the cause of the lack of loyalty of shopping members, and 3) To find out the efforts taken by the cooperative management to retract the loyalty of shopping members. The research method used is qualitative, the researcher tries to build rational arguments about everything, to explore the problems that cause 212 Mart to fail to develop, especially 212 Mart Bojongkulur. Data collection techniques in this study using observation, interviews, and documentation. The results of this study indicate that the factors causing the failure of 212 Mart Bojongkulur in terms of member loyalty are the lack of commitment from members to shop at 212 Mart, caused by the lack of understanding of members about the cooperative concept, most cooperative members only become investors, the goods at 212 Mart are expensive, more expensive than the market price, and the available goods are incomplete.